2019
DOI: 10.1016/j.wasman.2019.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of additively printed rare-earth bonded magnets

Abstract: In this work, we describe an efficient and environmentally benign method of recycling of additive printed Nd-Fe-B polymer bonded magnets. Rapid pulverization of bonded magnets into composite powder containing Nd-Fe-B particles and polymer binder was achieved by milling at cryogenic temperatures. The recycled bonded magnets fabricated by warm compaction of ground cryomilled coarse composite powders and nylon particles showed improved magnetic properties and density. Remanent magnetization and saturation magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Big area additive manufacturing (BAAM) is a system developed by Cincinnati Inc. to fabricate large parts via a material extrusion method which has produced bonded Nd-Fe-B magnets with attractive properties. [16][17][18][19][20][21][22] BAAM deposits layers of molten thermoplastics with magnet particles by extruding the material through a nozzle. The thermoplastic solidifies rapidly after deposition, allowing a large magnet to be built quickly.…”
Section: D Printing Of Bonded Magnet Via Binder-jet and Extrusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Big area additive manufacturing (BAAM) is a system developed by Cincinnati Inc. to fabricate large parts via a material extrusion method which has produced bonded Nd-Fe-B magnets with attractive properties. [16][17][18][19][20][21][22] BAAM deposits layers of molten thermoplastics with magnet particles by extruding the material through a nozzle. The thermoplastic solidifies rapidly after deposition, allowing a large magnet to be built quickly.…”
Section: D Printing Of Bonded Magnet Via Binder-jet and Extrusionmentioning
confidence: 99%
“…They found that the powders recycled via the hydrogen decrepitation performed better than the powder recycled via mechanical milling, although the remanence and coercivity degraded for both methods-with coercivity degrading the most. Gandha et al 18 reported on recycling waste bonded magnets by pulverizing thermoplastic bonded magnets in liquid nitrogen and then warm- compacting the powders to remake bonded magnets. The approach used by the authors yielded magnets having B r , H c , and (BH) max in the range 96-104%, 90-96% and 86-100%, respectively, compared to the waste bonded magnet being recycled.…”
Section: Reprocessing/remanufacturing/refurbishing Of Permanent Magnetsmentioning
confidence: 99%
“…This is, however, more difficult here, as these alloys oxidize easily in air, hence their covering with a protective coating. Various groups have therefore reported a general process that first performs a hydrogen exposure, which creates a volume expansion of the magnet as metal hydrides are formed [205][206][207][208][209][210]. This allows the casing to break, and the alloy to turn easily into fine powder.…”
Section: Rare-earth Elementsmentioning
confidence: 99%
“…This process also has the advantage that, if carefully performed, it protects the alloy from oxidation [211]. Additional milling, sometimes at cryogenic temperatures, has also been reported [205]. Once hydrogen is removed, by heating in neutral atmosphere (~200 • C), one can then reprocess the powder via compaction (with additives, binder, reducing agents, etc.)…”
Section: Rare-earth Elementsmentioning
confidence: 99%
See 1 more Smart Citation